Development of Tanggui Craftsmen In Kuin Utara In 2010-2019: Perkembangan Pengrajin Tanggui di Kuin Utara Tahun 2010-2019 - Siti Ismirat Purnama Sari Rush; Subroto, Wisnu; Mansyur, Mansyur (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to determine the beginning of the existence and development of tanggui craftsmen in North Kuin in 2010-2019. The method used in this research is the historical method. Historical research steps are used to obtain data related to the development of Tanggui craftsmen, starting from source collection (Heuristics), Criticism, Interpretation, and Historiography. At the data collection stage (Heuristics), primary and secondary data are obtained from oral sources through interviews and written sources obtained from books, journals and theses, as well as tangible sources from Tanggui craftsmen. then the source criticism stage is carried out to determine the authenticity of the source, then interpretation and finally historical writing or historiography. The results of this study are the beginning of the existence and development of Tanggui craftsmen in North Kuin from 2010 to 2019 started by parents and continued by their children when they were young to increase pocket money and continue into adulthood. In its development, tanggui craftsmen experienced several changes, namely in terms of the economy, wages increased in response to the high demand for tanggui handicraft products when the harvest season arrived. Tanggui craftsmen in North Kuin have recently faced changes, namely experiencing an increase in wages from the initial 70 thousand to 80 thousand per kudi. Usually, the craftsmen collect their wages once a month. Although Tanggui wages have increased, this is not a reason for Tanggui craftsmen to stay until finally they choose to quit due to old age and some craftsmen choose to switch professions.